2013
DOI: 10.1002/chem.201203625
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Luminescent Ethynyl‐Extended Regioisomers of Borate Complexes Based on 2‐(2′‐Hydroxyphenyl)benzoxazole

Abstract: A series of thirteen luminescent tetrahedral borate complexes based on the 2-(2'-hydroxyphenyl)benzoxazole (HBO) core is presented. Their synthesis includes the incorporation of an ethynyl fragment by Sonogashira cross-coupling reaction, with the goal of extending the conjugation and consequently redshifting their emission wavelength. Different regioisomers, substituted in the 3-, 4-, or 5-position of the phenolate side of the HBO core, were studied in order to compare their photophysical properties. The compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 83 publications
4
47
0
3
Order By: Relevance
“…Although weakly luminescent in CH 2 Cl 2 ( λ abs = 410 nm, λ em = 502 nm, Φ = 0.03), HBO borate complex 10 lightens up in THF and CH 3 CN ( λ abs = 388 nm, λ em = 482 nm, Φ = 0.23 and λ abs = 393 nm, λ em = 553 nm, Φ = 0.11). This behavior is reminiscent to that observed in the corresponding monoethynyl‐extended borate complex substituted by a single p ‐di‐ n ‐butylaminophenylacetylene fragment in the 3‐position; the luminescence of this species was fully quenched in CH 2 Cl 2 owing to strong ICT, but this species was emissive in other solvents 10b. To obtain more insight into this ICT process, we recorded optical data in CH 2 Cl 2 after bubbling HCl into the solution, which resulted in a significant blueshift in the absorption and emission and a major increase in the quantum yield ( λ abs = 386 nm, λ em = 448 nm, Φ = 0.36; Figure 7, b).…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Although weakly luminescent in CH 2 Cl 2 ( λ abs = 410 nm, λ em = 502 nm, Φ = 0.03), HBO borate complex 10 lightens up in THF and CH 3 CN ( λ abs = 388 nm, λ em = 482 nm, Φ = 0.23 and λ abs = 393 nm, λ em = 553 nm, Φ = 0.11). This behavior is reminiscent to that observed in the corresponding monoethynyl‐extended borate complex substituted by a single p ‐di‐ n ‐butylaminophenylacetylene fragment in the 3‐position; the luminescence of this species was fully quenched in CH 2 Cl 2 owing to strong ICT, but this species was emissive in other solvents 10b. To obtain more insight into this ICT process, we recorded optical data in CH 2 Cl 2 after bubbling HCl into the solution, which resulted in a significant blueshift in the absorption and emission and a major increase in the quantum yield ( λ abs = 386 nm, λ em = 448 nm, Φ = 0.36; Figure 7, b).…”
Section: Resultsmentioning
confidence: 54%
“…Excitation in the lower‐energy band of HBO borate complex 3 ( λ abs = 384 nm) leads to one emission band centered at 439 nm ( Φ = 0.21, Figure 5). This is a slight redshift relative to the emission band of the HBO borate monoethynyltrimethylsilyl‐extended at the 5‐position ( λ abs = 366 nm, λ em = 427 nm, Φ = 0.31) 10b. Finally, the excellent match between absorption and excitation spectra excludes the presence of aggregates in solution.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…As shown in Figure S11 (in the Supporting Information), we observed significant photobleaching for 1 – 3 under our experimental conditions whereas negligible changes were observed in the absorption spectrum of 4 upon irradiation, thereby indicating its excellent photostability. It is reported that boranils are prone to deboronation . On a similar note, the observed changes in the absorption spectra could be attributed to the elimination of the BF 2 moiety, resulting in the formation of the corresponding imines.…”
Section: Resultsmentioning
confidence: 53%